Scalability and replicability analysis of smart grid projects: Insights from the H2020 CROSSBOW project - Makrygiorgou, Despoina I.; Andriopoulos, Nikos; Georgantas, Ioannis; Rong, Jun; Moraitis, Ioannis; Calatayud, Esteban Pastor; Matoses, Manuel Serrano (Frontiers in Energy Research, 2023)
Scalability and Replicability Analysis (SRA) is usually performed for Smart Grid Architecture Model (SGAM) projects to assess the applicability of the proposed solutions in various regions, conditions, densities and sizes. In this framework, the replication and scaling-up roadmap of the Horizon 2020 (H2020) CROSSBOW project encompasses a variety of interesting aspects. This paper evaluates CROSSBOW’s results and their impact under various technical, regulatory, market, and social factors. The relevant methodology follows the literature and is properly adjusted to investigate at what level CROSSBOW concepts can be escalated and transferred to different scenarios and regions in an efficient and cost-effective manner. Limitations and challenges regarding scalability and replicability are also illustrated. The results depict the total impact of specific factors on scalability and replicability while useful conclusions are drawn. Lessons learnt from CROSSBOW are very insightful for the scalability and replicability of other upcoming projects.